The optimization of a race car intake system - Lešnik, Luka (JET on-line, 2017)
This paper deals with the optimization of a race car intake system in order to increase engine power output. The goal of optimization was to test how different lengths of intake trumpet influence air mass flow, pressure fluctuations and, consequently, the obtained engine-rated power and torque. Six trumpet lengths were tested using the 1-D AVL BOOST simulation program. The obtained numerical results of engine-rated power and torque were compared with the information obtained from the engine's manufacturer. The results of optimization indicate that the length of the intake trumpet significantly influences pressure fluctuation in the test engine intake system. At specific trumpet lengths, pressure fluctuation can help to increase air mass flow per engine cycle, which consequently influences engine-rated power and torque. It was found that shorter intake trumpets have an influence on a higher engine-rated power when operating at higher engine rotational speeds. Longer trumpets increase engine-rated torque at lower engine rotational speeds but decrease engine power at higher speeds. For the needs of competition, high peak engine power is desired, so the trumpets with 60 mm length were selected as optimal, because they have the highest peak engine power output at the desired engine speed.
Keywords: air trumpets; dirkalnik; engine intake design; motorji; nihanje tlaka; optimizacija; optimization; pressure fluctuation; sesalni sistemi; zračne trobente